Penerapan Media Big Book untuk Meningkatkan Kemampuan Pengenalan Kosa Kata Bahasa Arab terhadap Anak Usia 5-6 Tahun - Farah Dilla, Raudhah; Waryuzaq, Ira (ACIECE, 2019)
Language becomes the most important part in communicating locally and internationally. Arabic is a familiar language and should be learned by all Muslims. This is because Arabic is the language of the Koran and the Hadith which is a guide and guide for human life, especially Muslims. So that Arabic language needs to be introduced early on in children in interesting ways, one of them is in learning that is using big book media. This study uses classroom action research (CAR) with collaboration between researchers and teachers. Using the Kemmis and Mc.Taggart model which consists of four components namely, planning (plan), action and observation (Act and Observe), and reflection (reflect). This research was conducted in two cycles, due to the deficiencies found in cycle I. After doing the second cycle based on the reflection that existed on the first cycle, the results were obtained that the application of the big book media could improve Arabic vocabulary recognition abilities of children aged 5-6 years